The Effect of Tambora Extract (Ageratum Conyzoides) on the Healing of Incision Wouds (Vulnus Scissum) in White Rats (Rattus Norvegicus) of the Sprague Dawley Strain - Fhauzia Iin Aldini; Nunung Herlina; Taufik Septiawan (Jurnal Kesehatan Cendikia Jenius, 2025)
Wounds are a type of injury or damage, and wounds on body tissues caused by sharp objects can lead to bleeding. Tambora leaves (Ageratum conyzoides) are rich in saponins, flavonoids, polyphenols, and alkaloids, all of which have significant wound healing properties. This study aims to determine the effect of Tambora leaf extract (Ageratum conyzoides) on the healing process of incision wounds (Vulnus scissum) in white rats (Rattus norvegicus) of the Sprague Dawley strain with concentrations of 0.25%, 0.5%, and 1%, compared to a positive control using bioplacenton ointment. This study employed an experimental approach with a time series control group design. The sample consisted of four rats, three treated with Tambora leaf extract and one positive control, treated for 14 days. The results of the test using the Shapiro-Wilk normality test were used to analyze the data, with a p-value of <0.05, which showed a result of 0.10. Conclusion: The administration of Tambora leaf extract has the ability to heal wounds. In this study, Tambora leaf extract demonstrated effects such as anti-inflammatory, antibacterial, and antioxidant properties. The concentration showing the fastest healing time was P1 with a 0.25% formulation. It is recommended that Tambora Leaf Extract can serve as an alternative ointment for wound healing, as the plant is easily accessible.